The importance of the Swedish–Norwegian border citizens’ perspectives for bottom-up cross-border planning strategies - Braunerhielm, L. (2019)
There is political interest in Sweden’s proximity to Norway, which is reflected in the regional policy focusing on developing business needs. As such, proximity at the regional level is simply expected to generate economic growth. The authors propose a holistic approach to spatial planning in a Swedish–Norwegian border region in place of the simplistic economic perspective. The aim of the article is to highlight the importance of adopting a bottom-up cross-border planning perspective that is based on the perceptions of the border region residents by showing that the proximity of Norway is important to communities in Värmland Province, on the border with Norway, in a different way from how regional authorities and policymakers perceive it. The authors used a qualitative method in their study. They found that residents were more interested in the individual, social, and cultural opportunities of the border, while authorities stressed traditional growth strategies. In conclusion, the authors recommend that policymakers should implement a bottom-up cross-border planning strategy (CBPS) in Värmland that includes the residents’ perspective, as a reinforcement of place-based policy approaches.